(untitled) - Baker, Donna (Childrens Press, 1977)
Biography of Frederic Remington, who spent much of his life using art to document the emerging West.
Includes index.
Keywords: Remington, Frederic; 1861-1909; Juvenile literature; Remington, Frederic; 1861-1909; Artists